Investigating the challenges and barriers of promoting national philanthropy in the charity area: a mixed study - Parvaresh , Masoudeh; Taboli, Hamid; Ziaaddini , Mohammad (Social Determinants of Health, 2023)
Background: Nowadays, charitable activities are considered as one of the most important strategies to reduce poverty and respond to social deprivation. Although many charitable organizations and institutions have been established to organize charitable affairs, the functioning of these centers and organizations is still associated with many barriers. Thus, this study was designed and implemented with the aim of investigating the challenges and barriers of promoting national philanthropy in the area of charity, considering the role of various governmental and social institutions. Methods: This mixed study was conducted using two quantitative and qualitative phases. The quantitative phase included a descriptive-cross-sectional study that was conducted on 300 employees of the Imam Khomeini Relief Committee Organization in Kerman province, and the qualitative phase was conducted using the institutional mapping method. The participants in this section included experts in the philanthropy sector at the level of Kerman province. Results: The results of this study revealed that the mean score of the participants in the organizational performance scale was estimated at 118.74±14.74. In the qualitative section, the results showed that policy-making takes place in the public sector regardless of the quality of its implementation, and regarding the non-governmental organizations and charitable organizations, the results indicate their non-participation in decision-making and policy-making. Conclusion: The present research indicated that there are various barriers in the area of national philanthropy, and it is recommended that institutions and organizations operating in the relevant areas pay attention to the identified factors.